Presence of langerhans cells, regulatory T cells (Treg) and mast cells in asymptomatic apical periodontitis - Mariana Lobo BERGAMINI; Andressa Pinto MARDEGAN; Catharina Simioni DE ROSA; Michelle PALMIERI; Dmitry José de Santana SARMENTO; Karen Renata Nakamura HIRAKI; André Luiz Ferreira COSTA; Bengt HASSÉUS; Peter JONASSON; Paulo Henrique BRAZ-SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Asymptomatic Apical Periodontitis is essentially an inflammatory disease of microbial aetiology. Association and function of the cell components involved, or specific inductive factors and growth mediators associated with development, maintenance and resolution of the periapical lesions are still unknown. The objective of this study was to evaluate the concentration of Regulatory T cells (FoxP3+; Treg), Langerhans cells (CD1a+; LC) and mast cells in asymptomatic apical periodontitis. 73 cases were selected: 30 periapical granulomas, 29 radicular cysts and 14 residual cysts. All groups were submitted to morphological analysis for classification of inflammatory infiltrate and thickness of the epithelial lining as well as to immunohistochemical analysis for detection of LC and Treg cells. Toluidine blue staining was used for detecting mast cells. Analysis showed higher mean numbers of LC (8.2 cells/0.2mm2), and Treg cells in radicular cysts (5.910 cells/0.2mm2). As for mast cells, it was found that radicular cysts had a higher mean number of these cells compared to other periapical lesions (12.68 cells/0.2mm2). The association between thickness of the epithelial lining and inflammatory cells showed that the presence of hypertrophic epithelium in radicular cysts presented higher density of LC. The number of LC and Treg cells play an important role in the control of the inflammatory micro-environment in periapical granulomas and radicular cysts, respectively. The presence of mast cells in radicular cysts may be associated with progression of the lesion. Knowledge regarding the inflammatory cell profile is therefore essential for a better understanding of the pathogenesis of asymptomatic periapical periodontitis.